Energy and conflict: Security outsourcing in the protection of critical energy infrastructures. (December 2015) - Zabyelina, Yuliya; Kustova, Irina
Attacks on oil and gas infrastructures by terrorists and criminals in places like Nigeria, Colombia, Iraq and Russia have amplified the vulnerability of critical energy infrastructures (CEIs) to deliberate physical attacks. Being unable or unwilling to protect CEIs, many national governments have made attempts to alleviate these vulnerabilities through outsourcing of security, i.e. contracting the responsibility to protect CEIs out to non-state actors. This article advocates the need to conceptualize security outsourcing in the domain of critical energy infrastructure protection (CEIP) in order to explain a variety of regulatory choices made by governments in this domain. Based on a qualitative analysis of four case studies, the article discusses various types of security outsourcing in the protection of CEIs, including the militarization of national oil companies, public–private partnerships and the involvement of international organizations and local social groups. The typology may serve as a tool of describing, classifying and evaluating various forms of security outsourcing. The findings of the article help to deconstruct the complexity of security outsourcing and capture some of the major contemporary trends in energy security.